Comparison of Anthropometric and Conic Beam Computed Tomography Measurements of Patients with and without Difficult Intubation Risk According to Modified Mallampati Score: New Markers for Difficult Intubation - Senol, D.; Ozbag, D.; Dedeoglu, N.; Cevirgen, F.; Toy, S.; Ogeturk, M.; Kose, E. (Wolters Kluwer Medknow Publications, 2021)
Background: The aim of this study was to compare the anthropometric and cone beam computed tomography (CBCT) measurements taken from risk-free and risky groups by using the modified Mallampati score (MMS). Patients and Methods: A total of 176 volunteers between the ages of 18 and 65 in four different MMS classes were included in the study. The patients in classes MMS I and MMS II were accepted as risk-free and the patients in classes MMS III and MMS IV were accepted as risky for intubation. The Mann-Whitney U test was performed on the data to compare the anthropometric and radiological measurements taken from the risk-free and risky groups. A receiver operating characteristic (ROC) analysis was applied to the parameters that had a statistically significant difference. Results: According to the analysis results, statistically significant differences were found in the neck circumference (NC), maximum interincisal distance (MID), thyromental distance (TMD) and sternomental distance (SMD) of the anthropometric measurements of men and women between the risk-free and risky groups (P < 0.05). In terms of CBCT measurements, the thickness of the tongue (TT), distance between the uvula and posterior wall of pharynx (U-Ph), distance between posterior nasal spine and nasopharvnx (Snp-Nph) and length of the epiglottis (LE) were found to have statistically significant differences between the risk-free and risky groups of men and women (P < 0.05). Conclusion: The NC, MID, TMD and SMD anthropometric measurements and TT, U-Ph, Snp-Nph and LE radiologic measurements were found to support MMS, which is one of the most widely used bedside intubation prediction tests. In addition to the inclusion of CBCT for intubation prediction, U-Ph and Snp-Nph radiologic measurements were added as difficult intubation markers.
Keywords: Airway; anthropometry; cone beam computed tomography; intubation; Mallampati